Problem formulation in mental health residential treatment: a single case analysis - Pino, Marco; Mortari, Luigina (Clueb, 2012)
This paper investigates an episode of interaction in a mental health residential centre in Italy, where a resident and a staff member manage a relational problem. The episode leads to an apparently paradoxical outcome: in spite of the fact that the resident has sought the staff members’ cooperation to make sense of the relational problem, she ends up being blamed for that problem. Adopting the approach of conversation analysis, the paper shows that this outcome is the result of the transition from a relational view, to a one-sided view of the problem. The practices employed to accomplish this transition reflect a set of contrasting concerns and goals, which the participants bring to bear on the interaction. Reflection about these aspects can sensitize the public to some of the intricacies and challenges entailed in the delivery of mental health residential treatment.